Dukungan Bandung Creative City Forum Terhadap Rintisan Usaha Baru Generasi Muda Kota Bandung: Studi Kasus pada Komunitas NGADUide sebagai Partner Eksternal BCCF - Ashila Dwiyanisa (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2017)
Bandung is known as a creative city and created a community of creative communities called Bandung Creative City Forum (BCCF). BCCF as a hub organization, BCCF is founded largely by Community, Individual, Creative Entrepreneur, Nonprofit and Creativity Creator in Bandung or whose field of work or activity intersect very closely with the world of creativity and innovation. BCCF provides opportunities to maximize their potentials, gain resources and support young entrepreneurs through networking and partnerships established by BCCF and NGADUide communities to create creative entrepreneurs, whether individuals or communities, especially for younger generations of Bandung to supporting the creative economy of Indonesia.